Serum retinol-binding protein 4 and the risk of ischemic stroke in Egyptian patients with hypothyroidism - Nearmeen M Rashad; Hanan M Sabry; Samir A Afifi; Maha A Fathy; Amira M El-Helaly; Haitham E.Mohamed (SpringerOpen, 2019)
Objective Ischemic stroke (IS) is one of the major causes of disability and death worldwide. Effective prevention remains the best approach to reduce the burden of stroke. Adipokines can serve as a key messenger to central energy homeostasis and metabolic homeostasis. Retinol-binding protein 4 (RBP4), a retinol transporter, is elevated in insulin resistance. Controversy exists regarding the role of RBP4 in thyroid diseases. The objective of this study was to evaluate serum RBP4 in patients with hypothyroidism and to assess the association of serum RBP4 with susceptibility of IS. Patients and methods This case-control study included 50 healthy individuals as a control group and 90 patients with hypothyroidism, who were stratified into two subgroups: patients with IS and patients without IS. All participants were subjected to history taking and clinical, laboratory, and radiological evaluation. Results Serum RBP4 levels were significantly higher in hypothyroid patient, especially patients with IS, compared with the nonstroke group. Interestingly, serum RBP4 level was positively correlated with vascular and metabolic risk factors. Moreover, diastolic and systolic blood pressures, triglyceride, free T3, as well as thyroid-stimulating hormone, were independently correlated with serum RBP4 by linear regression analysis test. The diagnostic power of serum RBP4 level in differentiating hypothyroidism from controls was revealed at the cutoff value of 12.25, with area under the curve of 0.909 (95% confidence interval: 0.861-0.957). However, the diagnostic power of serum RBP4 level in differentiating hypothyroid patient with IS from those without stroke was revealed at the cutoff values of 11.4, with area under the curve of 0.822 (95% confidence interval: 0.737-0.906). In conclusion, the higher levels of serum RBP4 in hypothyroidism, especially in patients with IS, were associated with metabolic and glucose abnormalities, and thus, it could be used as a promising predictive biomarker of IS in hypothyroidism.